(3GdeZfj aj GdHjWQIs - (3YeQ Hf jhSa Hf YeQ Hf Ydj Hf QShd, CHh MaU, eegO GdOjf, Gdedc GdCTQa,J (B696 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3agPG cJGH eNJUQ LeYfGg ajeG LQHfGg (B((3h(B) (3LQHg Cgd GdNHQI ef MceGA GdNjd ef Cgd Gdjef s
(3BNQgG (B:s
(3cjG dWjakG NajakG JQajbkG MJi jefY GdhQe Cf jWdY Edi SGFQ CQLdgG , aEfg Se jVQgG Pdc Ef TGA Gddg JYGdi s
(3hgh JSYjf HGHkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B6s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B236 s
Keywords: (3GdWHs